1980
DOI: 10.1152/ajprenal.1980.239.5.f478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PTH, ADH, and cyclic AMP on distal tubular Ca and Na reabsorption

Abstract: Tubular microperfusion experiments were performed in rats to examine the effects of thyroparathyroidectomy (TPTX), parathyroid hormone (PTH), antidiuretic hormone (ADH), and cyclic AMP (cAMP) on distal tubular Ca, Na, and water reabsorption. TPTX caused a significant decrease in the Ca reabsorptive rate as compared to intact animals. PTH (5 U/kg; 2 U x kg-1 x h-1) replacement in TPTX animals restored Ca transport to control levels. Application of either cAMP (10(-3) M) or 8-(p-chlorophenylthio)-cyclic 3',5'-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 0 publications
4
28
0
Order By: Relevance
“…We also measured 22Na+ uptake at 1, 2, and 5 min after addition of 10 -8 M PTH but found no effect compared to untreated controls. Comparable observations have been made during in vivo and in vitro distal convoluted tubule microperfusion experiments where PTH increased calcium but not sodium absorption (12,34,38). Furthermore, increased sodium entry would be expected to depolarize distal convoluted tubule cells.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…We also measured 22Na+ uptake at 1, 2, and 5 min after addition of 10 -8 M PTH but found no effect compared to untreated controls. Comparable observations have been made during in vivo and in vitro distal convoluted tubule microperfusion experiments where PTH increased calcium but not sodium absorption (12,34,38). Furthermore, increased sodium entry would be expected to depolarize distal convoluted tubule cells.…”
Section: Discussionmentioning
confidence: 74%
“…However, certain physiological, pharmacological, or pathological influences are known to dissociate one from the other. PTH, for instance, reduces renal calcium exere-tion without a change in sodium excretion (10,12,38). Although the mechanisms responsible for the dissociation are not known definitively, they all proceed in distal convoluted tubules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that parathyroid hormone stimulates calcium entry in primary cell cultures ofcortical thick ascending limb and distal convoluted tubule cells by activating dihydropyridine-sensitive calcium channels (16). Activation of such dihydropyridine-sensitive calcium channels in apical plasma membranes is consistent with the physiological effect ofparathyroid hormone to increase the rate oftransepithelial calcium transport ( 17,18). Taken together, these observations suggested a plausible mechanism by which thiazide diuretics might stimulate calcium transport.…”
Section: Introductionmentioning
confidence: 66%
“…Although there is evidence for a physical interaction, these data do not explain all the phenomena associated with ENaC. For example, amiloride-sensitive sodium transport is stimulated by cAMP in renal distal tubules, even though these cells express both CFTR and ENaC (5,6). An alternative possibility is that the loss of some cellular signal in CF airway epithelia that normally serves to down-regulate sodium absorption may play a role in initiating the increased rate of sodium absorption.…”
Section: Introductionmentioning
confidence: 86%